2014
DOI: 10.1182/blood.v124.21.3170.3170
|View full text |Cite
|
Sign up to set email alerts
|

Splenic Irradiation and a Reduced-Intensity Conditioning Regimen Prior to Allogeneic Stem-Cell Transplantation for Myelofibrosis

Abstract: Background: Allogeneic hematopoietic stem cell transplantation (HSCT) remains the only curative option for patients with myelofibrosis (MF). Reduced-intensity conditioning (RIC) regimens have been used to extend this therapy to older and sicker patients. Splenectomy prior to HSCT for MF has been shown to enhance neutrophil engraftment and decrease transfusion requirements, but has a reported operative mortality of 9% or higher. Splenic irradiation (sXRT) has been historically used as a palliative treatment in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Reports on the role of SI prior to ASCT for myelofibrosis are sparse and included small groups of patients or case studies [ 8 , 9 , 16 , 17 ]. Eight patients with MF received median splenic radiation dose of 450 cGy within median of 2 weeks prior to ASCT in Kalman study [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reports on the role of SI prior to ASCT for myelofibrosis are sparse and included small groups of patients or case studies [ 8 , 9 , 16 , 17 ]. Eight patients with MF received median splenic radiation dose of 450 cGy within median of 2 weeks prior to ASCT in Kalman study [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results were then confirmed by others. Administration of SI as a part of reduced-intensity conditioning at doses ranging from 300 to 500 cGy in three patients was found to be feasible with acceptable toxicity [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of splenic irradiation before HSCT in MF patients is not well established and has been investigated in only a few small studies. 13,14 Nonetheless, low-dose splenic irradiation was found to significantly reduce spleen size (median decrease 10 cm, 36%), and was a safe and well-tolerated adjunct to HSCT in 8 hypersplenic patients with MF. 13 In a more recent study, Helbig et al 15 assessed the outcome of pretransplantation splenic irradiation in 44 patients with MF who underwent allogeneic HSCT.…”
Section: Radiotherapy As An Alternative To Splenectomymentioning
confidence: 96%
“…Splenic irradiation (SI) may also be used to reduce the spleen size and related symptoms; there are only few small studies on SI prior to transplant in MF patients ( 22 , 23 ). It was demonstrated that SI alleviates splenic discomfort and reduces spleen size in a majority of MF patients, with a median duration of response of 6 months ( 24 ).…”
Section: How To Deal With Splenomegalymentioning
confidence: 99%